Augmented Education in the Global Age Artificial Intelligence and the Future of Learning and Work - Araya, Daniel; Marber, Peter (Taylor & Francis, 2023)
Augmented Education in the Global Age: Artificial Intelligence and the Future of Learning and Work is an edited collection that explores the social impact of Artificial Intelligence over the coming decades, specifically how this emerging technology will transform and disrupt our contemporary institutions. Chapters in this book discuss the history of technological revolutions and consider the anxieties and social challenges of lost occupations, as well as the evolution of new industries overlapping robotics, biotechnology, space exploration, and clean energy. Chapter authors unpack the nature of augmented education, from revamping curriculum and personalizing education, to redesigning workplace learning for an algorithmic era. Ultimately the book discusses policy and planning for an augmented future, arguing that work and learning are undergoing a metamorphosis around creativity and innovation amid a new global era and the race against automating technologies. Bringing together expert perspectives from around the world, this exciting, informative collection of research and analysis helps educators, policymakers and analysts navigate the future of work and learning amid rapid and accelerating technological change.